Diagnostic and therapeutic efficacy of double-balloon endoscopy in patients with small intestinal diseases: Single-center experience in 513 procedures - Mesut Akarsu; Seda Akkaya Özdinç; Aygül Çeltik; Hale Akpınar (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Double-balloon endoscopy (DBE) is a technique that enables the evaluation and treatment of small intestinal diseases. The aim of the study was to evaluate the indications, therapeutic interventions, complications, and safety and to describe the experience with DBE in Turkish patients. Materials and Methods: Four hundred twenty consecutive patients undergoing DBE were included in our study. Demographic features, indications, diagnostic findings, therapeutic interventions, complications, and technical aspects of the procedure were recorded. A total of 513 DBEs were carried out. Results: In all, 420 patients underwent a total of 513 DBE procedures (369 (72%) oral and 144 (28%) anal). The most common clinical indications were obscure bleeding (26%), abdominal pain (25.2%), anemia (20%), chronic diarrhea (10.5%), and inflammatory bowel diseases (5.2%). A proper diagnosis was obtained or confirmed in 222 of 420 patients (52.3%). Ulcers/erosions (23.6%), vascular lesions (8.1%), and polyps/tumors (7.4%) represented the most common endoscopic findings. Perforation occurred in one patient as a complication after polypectomy. No major complications due to sedation occurred. Conclusion: Double-balloon endoscopy is effective for the diagnosis and treatment of small intestinal diseases. Therapeutic interventions carried out by DBE seem to be useful and safe.